Admirable dishonesty in medical practice - McCabe, Matthew S. (Communication and Medicine, 2014)
Historically, the ethics of dishonesty within the physician-patient relationship has been analyzed largely from the Deontological and Consequentialist views. In this essay I offer a new exploration of dishonesty from the recently developed Virtue Ethics of Care perspective. First, I will explain and justify a general prescription for honest conduct within the relationship. Next, I will explore the conditions under which the Virtue Ethics of Care would find acts of dishonesty in medical practice to be admirable. Here, the moral distinction between lying and deception will be discussed. Then, three special contexts in medical practice, paternalistic dishonesty, patient dishonesty, and dishonesty toward third party members influential to the physician-patient decision making process, will be analyzed. I will close with a discussion of the role of trust in the relationship and how it acts to prevent the Virtue Ethics of Care from sliding down the path toward objectionable acts of dishonesty.